PERAN PERAWAT DALAM IDENTIFIKASI DINI DAN PENATALAKSANAAN PADA ACUTE CORONARY SYNDROME - Nur Ainiyah (Universitas Nahdlatul Ulama Surabaya, 2015)
The role of nurses in the early identification and treatment on Acute Coronary Syndrome. Introduction : Acute Coronary Syndrome ( ACS ) is an emergency in the coronary arteries . Nurses are very necessary to provide treatment of acute coronary syndrome accurately and precisely both prehospital and intrahospital . Methods: The literature search from April 2006 through April 2016 in MEDLINE, NCBI, CINAHL using key words : Acute Coronary Syndrome, treatment and does not restrict the research sampling. Results: Based on the literature review 10 obtained the enforcement of early diagnosis of ACS should be done immediately, which can be done by looking of three criteria: chest pain, ECG changes and sign biochemical (biomarker serum). Discussion: The nursing care must have role in the management of ACS. Therefore the quality of care given depends on the knowledge and skills of nurses both prehospital and intrahospital